Essential endodontology : prevention and treatment of apical periodontitis - Ørstavik, Dag (John Wiley & Sons, 2020)
"The authoritative reference that continues to present a systematic analysis of the scientific basis of endodontology The third edition of Essential Endodontology: Prevention and Treatment of Apical Periodontitis has been revised and updated to include the most recent developments in the field, maintaining its position as the major scientific treatise of apical periodontitis. Making an often-complex subject more digestible, the book explores the scientific basis of endodontology, adopting a systematic analysis of the available clinical and laboratory evidence. Promoting apical periodontitis as a disease entity, the comprehensive third edition focuses on its biology and clinical features, enabling the reader to have a better understanding of its diagnosis, prevention and treatment. In addition to thorough updates and full colour illustrations throughout, a new chapter on regenerative endodontics has been added to this edition. Written with a focus on the scientific basis of endodontology Includes a new chapter on regenerative endodontics presents the most current information and major developments in this fast-moving field provides helpful learning outcomes in each chapter contains full colour illustrations, enriching the text features contributions from a noted panel of international experts, including new contributors from across the globe Regarded as a vital companion to the pursuit of excellence in postgraduate and specialist education, Essential Endodontology is an indispensable and accessible resource for practicing endodontists, postgraduate students of endodontology and those seeking professional certification in endodontology"--